Enhanced Susceptibility to Kainate-Induced Seizures, Neuronal Apoptosis, and Death in Mice Lacking Gangliotetraose Gangliosides: Protection with LIGA 20, a Membrane-Permeant Analog of GM1 - Wu, Gusheng (J Neurosci, 2005)
Knock-out (KO) mice lacking gangliotetraose gangliosides attributable to disruption of the gene for GM2/GD2 synthase [GalNAcT (UDP-N-acetylgalactosamine:GM3/GD3 β-1,4-N-acetylgalactosaminyltransferase; EC 2.4.1.92)] are revealing key neural functions for the complex gangliosides of brain. This study has found such animals to be highly susceptible to kainic acid (KA)-induced seizures in terms of both seizure severity and duration. Intraperitoneal injection of 25 mg/kg KA produced status epilepticus for ∼200 min in normal mice or heterozygotes and more than four times longer in the KO mice. The latter group suffered ∼30% mortality, which increased to ∼75% at dosage of 30 mg/kg KA, compared with 10-14% for the other two genotypes at the latter dosage. Nissl staining and terminal deoxynucleotidyl transferase-mediated biotinylated UTP nick end labeling assay revealed substantial deterioration of pyramidal neurons attributable to apoptosis in the KO hippocampus, especially the CA3 region. Seizure activity in the KO mouse was only moderately diminished by intraperitoneal injection of GM1 ganglioside, whereas LIGA 20, a semisynthetic analog of GM1, substantially reduced both seizure severity and cell damage. The potency of LIGA 20 was correlated with its enhanced membrane permeability (compared with GM1), as seen in the increased uptake of [(3)H]LIGA 20 into the subcellular fractions of brain including cell nuclei. The latter finding is consonant with LIGA 20-induced restoration of the Na(+)/Ca(2+) exchanger located at the inner membrane of the nuclear envelope in KO mice, an exchanger dependent on tight association with GM1 or its analog for optimal activity. These results point to a neuroprotective role for GM1 and its associated exchanger in the nucleus, based on regulation of Ca(2+) flux between nucleoplasm and nuclear envelope.